2014
DOI: 10.1055/s-0034-1368723
|View full text |Cite
|
Sign up to set email alerts
|

Cooling during Exercise in Temperate Conditions: Impact on Performance and Thermoregulation

Abstract: Exercise-induced increase in core body temperature may lead to the development of hyperthermia (>40.0°C) and/or decreased performance levels. This study examined the effects of wearing a cooling vest during a 5-km time trial on thermoregulatory responses and performance. 10 male masters athletes (42±10 years) performed a 5-km time trial on a motorized treadmill in a climate chamber (25°C, 55% relative humidity) with and without a cooling vest. Split times, heart rate, core-, skin- and cooling vest temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 25 publications
3
51
0
1
Order By: Relevance
“…Finally, the heat‐related performance decrement observed in temperate conditions is small relative to exercise under hotter conditions and the improved thermoregulatory capability may have been insufficient to meaningfully impact upon this. A recent study has shown that wearing a cooling vest did not significantly impact on exercise performance in temperate conditions (25 °C, 55% RH), despite reductions in heart rate, skin temperature and improved thermal comfort (Eijsvogels et al., ). It should be noted that while STHADe has been shown to be ergogenic under hot conditions (Garrett et al., ), ergogenic effects under temperate conditions have not been demonstrated and it may be that a longer HA program is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the heat‐related performance decrement observed in temperate conditions is small relative to exercise under hotter conditions and the improved thermoregulatory capability may have been insufficient to meaningfully impact upon this. A recent study has shown that wearing a cooling vest did not significantly impact on exercise performance in temperate conditions (25 °C, 55% RH), despite reductions in heart rate, skin temperature and improved thermal comfort (Eijsvogels et al., ). It should be noted that while STHADe has been shown to be ergogenic under hot conditions (Garrett et al., ), ergogenic effects under temperate conditions have not been demonstrated and it may be that a longer HA program is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is unexpected, because the thermal load is larger in hot ambient conditions, 58 which should facilitate the potential benefits of cooling. However, there is a large variation in performance benefits in the studies performed in moderate ambient conditions, ranging from a small non-significant negative effect (−0.6%, ES = 0.08) 49 to a very large positive effect (51%, ES = 1.17) 57 of per-cooling. This variation may possibly be explained by methodological differences in the exercise protocol and outcome measures, as a subjective outcome (rate of perceived exertion) was used as a surrogate for exercise intensity and may therefore influence the time to exhaustion 52 .…”
Section: Per-coolingmentioning
confidence: 99%
“…Due to practical feasibility and sporting regulations, less cooling techniques can be applied during exercise compared to pre-cooling. Consequently, the effects of per-cooling were investigated using cooling packs, 46-48 cooling vests, 49,50 cold water/ice slurry ingestion, 37,51 facial wind or water spray cooling 52,53 and menthol cooling 54-56 . Interestingly, menthol cooling could be applied as a mouth rinse, a gel on the face or as a spray on the clothing of the athlete.…”
Section: Per-coolingmentioning
confidence: 99%
See 2 more Smart Citations